Experiential Programming for Resorts - Matthew Miller; Jannatul Rafia-Tracy (Tourism and Hospitality)
This study investigates the influence of experiential programs (EPs) on enhancing consumer experience offerings at luxury resorts. EPs encompass a variety of activities, amenities, and services designed to immerse consumers in the local culture, scenery, and authenticity. The research focuses explicitly on EPs related to fitness, evening entertainment, children’s activities, and personalized experiences. By analyzing data from 30 resorts, significant trends and typologies within each category of EP emerged, highlighting the diverse ways in which resorts meet consumers’ desires for immersive and status-enhancing experiences. Valuable insights were gained through semi-structured interviews with two hoteliers, providing a deeper understanding of the strategic integration of EPs. Fitness EPs highlight activities, including hiking and yoga, whereas evening entertainment encompasses experiences like mixology, music, and astronomy education. For children, EPs prioritize cultural immersion through hands-on experiences, while personalized EPs—including romance packages and private dining—allow for consumer exclusivity. The research underscores how these EPs align with contemporary trends in conspicuous consumption, where luxury resorts leverage unique, high-quality, and culturally rich experiences to reinforce affluence and societal standing. The findings emphasize that EPs are a vital strategy for luxury resorts to differentiate themselves in a competitive market, enhancing consumer satisfaction, loyalty, and positive self-image.